ANALISIS TINGKAT KEPUASAN MASYARAKAT SURAKARTA TERHADAP FLY OVER PURWOSARI SURAKARTA - Yohannes Lulie; Hosea Endru Setiawan (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2022)
Abstract: Transportation is growing very rapidly along with the times, the development of transportation can cause traffic jams, especially land transportation. Surakarta is one of the cities experiencing severe congestion in the flow of traffic, due to the large number of railroad crossings that make traffic jammed, one of which is in Purwosari, Surakarta. Due to frequent traffic jams at that location, the Fly Over Purwosari Surakarta was built, the fly over itself is one of the structures that avoids traffic jams. During development, there are many pros and cons, therefore research on the satisfaction and comfort of fly over users is one thing that must be considered, so that the level of satisfaction can be a benchmark whether the fly over has succeeded in its function. This research was conducted by distributing a questionnaire form to 100 riders who crossed the Fly Over Purwosari Surakarta. Validity tests, reliability tests, and Importance Performance Analysis (IPA) tests were carried out with the help of the SPSS (Statistical Product and Service Solutions) version 25 program and Microsoft Excel 2016. In analyzing the satisfaction level, there are several aspects such as safety, road conditions, guarantees for road users, accessibility, and mobility. The results of this study are able to show that the driver is quite satisfied the completeness and clarity of road markings, the accessibility of the lane, as well as the completeness and clarity of traffic signs. Then for performance that needs to be improved again is street lighting.